(untitled) (REVISTA NODO, 2015)
In each historical period architecture itself has been linked to scientific thought. At the end of the twentieth century, the sciences of complexity were explicity banckrupt in their universal knowledge models. The complex are valued, however, and uncertainty as positive developments in this kind of flight to the future, their complementarity and antagonism as a dialectical and controversial opposition to any idea of architectural composition is also proposed, showing contradictions and ambiguities. This approach recognizes the complexity structure a new collusion, and finds the fundamental problems of reality, uncertainty and contradiction, where it exceeds the possibilities of human logic, which shows the transition from simple to complex. In turn, the principles of organization for architecture involve forgetting canons and precepts as well as predominance and wholes, so that a kind of combinatorial activity arises in their experimentation of new methodological. Finally, one is able to reflect and understand the ambivalence about space, that is, the inherent complexity that is at the heart of science and architecture.